Dimensi Psikologis dalam Ibadah-Ibadah Agama Islam - Khairina; Cindy Oktariani; Anis Sunnai Reyin3; Fahmi Al Munawwar; Raihan Avlbani Dalimunthe; Ramadan Lubis (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Worship in Islam has a much broader dimension than juyst rituals, including psychological aspects that have a positive impact on individuals and society. This article examines the psychological dimensions of two main acts of worship, prayer and zakat, which function as a bridge to strengthen the vertical relationship with Allah (hablum minallah) and horizontal relationships with fellow human beings (hablum minannas). Using a qualitative approach involving in-depth interviews and literature studies, this study explores the role of these two acts of worship in supporting mental, emotional, and spiritual well-being. The research findings show that prayer offers a therapeutic effect that creates peace of mind, emotional stability, and increased self-discipline. On the other hand, zakat fosters empathy, happiness in sharing, and social awareness that contribute to reducing anxiety related to social inequality. The combination of prayer and zakat forms a positive mindset, increases optimism, and builds a more patient and humble character. This study concludes that prayer and zakat are not only religious obligations, but also effective tools to improve the quality of life of individuals and communities. This research broadens insights into how Islamic teachings can be a solution to mental and emotional challenges in the modern era.